(untitled) (International Educators Conference, 2025)
The Fergana Valley, located in the heart of Central Asia, has long been considered a fertile and strategic area of trade, agriculture, and cultural exchange. Historically, it was one of the important cities associated with Sogdiana, the ancient Iranian civilization that flourished along the Silk Road.